Structurally Diverse Nitric Oxide-Releasing Poly(propylene Imine) Dendrimers - Lu, Yuan (2011)
Structurally diverse secondary amine-functionalized poly(propylene imine) (PPI) dendrimers capable of tunable nitric oxide (NO) release were synthesized in a straightforward, one-step manner using ring-opening or conjugate-addition reactions with propylene oxide (PO), styrene oxide (SO), acrylonitrile (ACN), poly(ethylene glycol) methyl ether acrylate (average Mn = 480) (PEG) or 1,2-epoxy-9-decene (ED). N-Diazeniumdiolate nitric oxide donors were formed on the resulting secondary amine-functionalized G2–G5 PPI dendrimers by reaction with NO gas in basic solution. The NO storage and release kinetics for the resulting dendritic scaffolds were diverse (0.9–3.8 μmol NO/mg totals and 0.3 to 4.9 h half lives), illustrating the importance of the exterior chemical modification (e.g., steric environments, hydrophobicity, etc.) on diazeniumdiolate stability/decomposition. Tunable NO release was demonstrated by combining two donor systems on the exterior of one macromolecular scaffold. Additionally, a mathematical model was developed that allows for the simulation of dual NO release kinetics using the NO release data from the two single NO donor systems. The approaches described herein extend the range and scope of NO-releasing macromolecular scaffolds by unlocking a series of materials for use as dopants in biomedical polymers or stand-alone therapeutics depending on the exterior modification.